Upaya meningkatkan aktivitas belajar siswa dengan menggunakan model pembelajaran student facilitator and explaining pada mata pelajaran IPS Kelas VII di SMP Negeri 03 Sukadana Kabupaten Kayong Utara - Ratih Lisma Purbayanti; Suherdiyanto Suherdiyanto; Ivan veriansyah (LPD IKIP PGRI Pontianak, 2022)
This study aims to determine the increase in student learning activities with the learning model student facilitator and explaining in social studies subjects for class VII at SMP Negeri 03 Sukadana, North Kayong Regency. This research is a classroom action research which consists of three meetings, namely pre-action, cycle I and cycle II. Each cycle has four stages. The techniques used in this research consist of direct observation techniques, direct communication techniques, and documentary study techniques. Data collection tools in this stud y used observation sheets, interview guidelines and documentation. The population and sample in this study were all class VIIB of SMP Negeri 03 Sukadana, Kayong Utara district, which consisted of 1 class with a total of 25 students. Sources of data obtained from observations will be analyzed quantitatively. Based on the research results, the results of this study indicate that using the student facilitator and explaining learning model can improve the learning activities of class VIIB students in social studies subjects at SMP Negeri 03 Sukadana, North Kayaong Regency. In the pre-action stage, the learning activities that appear are 46.66%, then in the first cycle stage the learning activities that appear are 68.26%, in the second cycle stage the learning activities that appear reach 86.66%. In the implementation of the second cycle of student learning activities are considered successful because the indicators of the success of student learning activities have been set with an achievement of 81%.